The Negative Effect of Job Insecurity in the Virtuous Cycle Between Trust in the Organization, Subjective Well-Being, and Task Performance in the Current Volatility, Uncertainty, Complexity, and Ambiguity Context - Stankevičiūtė, Živilė; Sanchez-Hernandez, M. Isabel; Staniškienė, Eglė (Frontiers in Psychology, 2021)
Over the past decade, job insecurity referring to the employees’ perceived threat to the continuity and stability of employment as it is currently experienced has become a hot topic. A general assumption, supported by the findings, is that job insecurity causes far-reaching negative consequences for the employee well-being and health, attitudes towards the job and organisation, and behaviours at work. However, the focus on behavioural outcomes, especially on employee performance at work, is still scant. Moreover, the literature remains fragmented concerning the impact of job insecurity on employee trust in the organisation and how the trust influences employee subjective well-being, which in turn, affects employee performance. Consequently, the link between job insecurity and subjective well-being needs more investigation. Trying to narrow the gap, the paper aims at revealing the linkage between job insecurity, trust in the organisation, subjective well-being and task performance. Quantitative data were collected in Lithuania. As predicted, the results revealed that job insecurity had a negative impact on trust in the organisation and employee subjective well-being. In case of linkage between job insecurity and task performance, the hypothesis was rejected. In general, these findings affirmed that job insecurity was a hindrance stressor, which needed to be considered when managing human resources in the current VUCA context.